Analisis Pengaruh Defisit Anggaran, Belanja Pemerintah Pusat, dan Utang Pemerintah terhadap Pertumbuhan Ekonomi di Indonesia Tahun 1990-2019 - Praycilia Elisabeth; FX Sugiyanto (Universitas Diponegoro, 2021)
In maintaining and increasing economic growth, it is necessary to have appropriate and effective policies so that the target of increasing economic growth every year can be achieved. This policy must be in line with various developments carried out to increase economic growth. However, high government spending will increase the budget deficit and also increase the need for financing through debt. This study uses the variable budget deficit, central government spending, government debt (SBN and ULN), and economic growth in Indonesia from 1990 to 2019. The analysis method used is time series data analysis with the Autoregressive Vector model (VAR) which aims to identify long-term relationships between variables and the Error Correction Model (ECM) which aims to analyze the longterm and short-term effects between variables. The results of research with the VAR model show that the variable deficit, government spending, government securities, and foreign debt have a one-way relationship with Gross Domestic Product. The results of the study with the ECM model show that the central government spending variable and Government Securities (SBN) have a positive and significant effect on gross domestic product (GDP) in the short and long term, and foreign debt has a negative and significant effect on GDP in the short and long term during the period 1990-2019. Based on this research, it can be concluded that the fiscal policy implemented in 2019 is a sustainable fiscal policy.